Maturity-onset diabetes of the young type 3 and premature ovarian insufficiency: chance or causality: a case report and literature review. (25th May 2022) - Alvarez, Mauricio; Rincon, Oswaldo; Alvarado, Alejandra; Puentes, Francisco
Abstract : Summary: We present the case of a 23-year-old patient with maturity-onset diabetes of the young type 3 (MODY 3) and premature ovarian insufficiency (POI). There is no known correlation between MODY 3 and POI, although POI can impair glucose metabolism, and MODY can cause microvascular complications such as POI. We did not find literature describing a correlation between these two pathologies nor did we find similar cases described in the literature. Learning points: Maturity-onset diabetes of the young type 3 (MODY 3) is an infrequent cause of diabetes that should be considered in young patients with atypical presentation of type 1 or type 2 diabetes. MODY 3 can be associated with microvascular complications of diabetes, which is why it is important to diagnose as early as possible. Impairment of glucose metabolism has been demonstrated in patients with premature ovarian insufficiency and menopause.